Electrode current collector and sodium bipolar electrode laminate

CN122992079APending Publication Date: 2026-10-27TOYOTA JIDOSHA KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202512019232.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-24
Filing Date
2025-12-30
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

根据专利文献1中所记载的钠离子电池,即使在使用碳材料作为负极活性物质的情况下,也能够抑制过放电循环寿命降低

Benefits of technology

[0021]根据本发明的方法,能够提供一种抑制了针孔及裂纹的产生的钠电池用电极集流体。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

Provided is an electrode current collector for sodium batteries in which the generation of pinholes and cracks is suppressed. The electrode current collector for sodium batteries of the present invention has, in order, a metal foil layer, a conductive resin layer, and an aluminum vapor deposition film layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an electrode current collector for sodium batteries and a sodium bipolar electrode laminate. Background Technology

[0002] A bipolar electrode stack is formed by stacking one or more bipolar electrodes, wherein the bipolar electrodes sequentially have a positive active material layer, a current collector layer, and a negative active material layer. Sodium bipolar electrode stacks are known as one type of bipolar electrode stack.

[0003] For example, Patent Document 1 discloses a sodium-ion battery comprising a positive electrode, a negative electrode, and a sodium-ion non-aqueous electrolyte. The negative electrode has a negative electrode active material and a negative electrode current collector made of aluminum or an aluminum alloy. According to the sodium-ion battery described in Patent Document 1, even when using carbon materials as the negative electrode active material, the reduction in over-discharge cycle life can be suppressed.

[0004] Furthermore, Patent Document 2 discloses an electrode current collector comprising, in sequence, a metal foil, a conductive resin layer, and a carbon particle layer. The conductive resin layer comprises a continuous phase and a dispersed phase. The continuous phase comprises a resin material, the dispersed phase comprises conductive particles, and the carbon particle layer comprises conductive carbon particles. According to the electrode current collector described in Patent Document 2, the metal content is reduced.

[0005] Patent Document 1: Japanese Patent Application Publication No. 2010-225525

[0006] Patent Document 2: Japanese Patent Application Publication No. 2024-088043 Summary of the Invention

[0007] As described in Patent Document 1, when the current collector layer is a single-layer structure of metal foil, the metal foil is relatively weak to bending, so pinholes or cracks are generated in a part of the metal foil, resulting in a liquid state. This may lead to a decrease in battery performance, such as reduced efficiency and lifespan.

[0008] Therefore, the object of the present invention is to provide an electrode current collector for sodium batteries that suppresses the generation of pinholes and cracks.

[0009] The present invention achieves the above objectives through the following technical solutions.

[0010] (Method 1)

[0011] An electrode current collector for sodium batteries comprises, in sequence, a metal foil layer, a conductive resin layer, and an aluminum vapor-deposited film layer.

[0012] (Method 2)

[0013] According to the electrode current collector of method 1, the thickness of the aluminum vapor-deposited film layer is 0.10 μm or more and 1.00 μm or less.

[0014] (Method 3)

[0015] According to the electrode current collector of method 1 or 2, the conductive resin layer comprises resin and carbon particles dispersed in the resin.

[0016] (Method 4)

[0017] The electrode current collector according to any one of methods 1 to 3, wherein the metal foil layer is an aluminum layer.

[0018] (Method 5)

[0019] A sodium bipolar electrode stack comprising an electrode current collector according to any one of embodiments 1 to 4.

[0020] Invention Effects

[0021] According to the method of the present invention, it is possible to provide an electrode current collector for sodium batteries that suppresses the generation of pinholes and cracks. Attached Figure Description

[0022] Figure 1 This is a schematic diagram illustrating the electrode stack of the embodiment. Detailed Implementation

[0023] The embodiments of the present invention will now be described in detail. However, the present invention is not limited to the following embodiments, and various modifications can be made within the scope of the spirit of the invention. Furthermore, in the description of the drawings, the same elements are labeled with the same symbols, and repeated descriptions are omitted.

[0024] <<Electrode Current Collectors for Sodium Batteries>>

[0025] The current collector for the sodium battery of the present invention comprises a metal foil layer, a conductive resin layer and an aluminum vapor-deposited film layer stacked sequentially.

[0026] The electrode current collector used in the above-mentioned sodium battery can suppress the generation of pinholes and cracks.

[0027] Traditional sodium batteries use a single-layer structure of metal foil as the electrode current collector. However, when using only metal foil as the electrode current collector, pinholes or cracks may form in a portion of the foil, leading to reduced battery performance.

[0028] Furthermore, when using an electrode current collector with a conductive resin layer on its surface, the contact between the conductive resin layer and the active material layer becomes unstable, which may lead to a decrease in initial charge-discharge efficiency. As described in Patent Document 2, by stacking a carbon particle layer on the surface of the conductive resin layer, the contact with the active material layer can be improved. However, this carbon particle layer reacts with sodium ions contained in the electrolyte of the sodium electrode stack, which may also lead to a decrease in initial charge-discharge efficiency.

[0029] In contrast, the electrode current collector of the present invention comprises a metal foil layer, a conductive resin layer, and an aluminum vapor-deposited film layer stacked sequentially. The conductive resin layer in the electrode current collector of the present invention improves the flexibility of the electrode stack, thereby suppressing pinholes or cracks in the electrode current collector. Furthermore, the presence of an aluminum vapor-deposited film layer on the surface of the conductive resin layer enhances the contact between the aluminum vapor-deposited film layer and the active material layer, thereby suppressing the aforementioned problems. Additionally, compared to the carbon particle layer, the aluminum vapor-deposited film layer is less likely to react with sodium ions contained in the electrolyte of the sodium electrode stack, thus reducing the likelihood of a decrease in initial charge-discharge efficiency.

[0030] In this invention, the thickness of the electrode current collector foil is not particularly limited, and can be 10.0 μm or more, 15.0 μm or more, 20.0 μm or more, or 30.0 μm or more, and can be 100.0 μm or less, 90.0 μm or less, 80.0 μm or less, or 70.0 μm or less.

[0031] <Metal Foil Layer>

[0032] In this invention, the metal foil layer is contained in the electrode current collector.

[0033] In this invention, the metal constituting the metal foil layer is not particularly limited and can be aluminum, copper, iron, stainless steel, or alloys thereof. In particular, when the metal constituting the metal foil layer is aluminum, that is, when the metal foil layer is an aluminum layer, both the metal foil layer and the aluminum vapor-deposited film layer of the electrode current collector of this invention contain aluminum. In sodium batteries, aluminum and sodium do not readily form alloys; therefore, the electrode current collector of this invention, in which both the metal foil layer and the aluminum vapor-deposited film layer are formed of aluminum, can be preferably used in sodium batteries.

[0034] In this invention, the thickness of the metal foil layer is not particularly limited and can be 10.0 μm or more, 15.0 μm or more, or 20.0 μm or more, and can be 50.0 μm or less, 45.0 μm or less, 40.0 μm or less, or 35.0 μm or less.

[0035] <Conductive resin layer>

[0036] In this invention, a conductive resin layer is contained within an electrode current collector. The conductive resin layer comprises resin and conductive fillers dispersed within the resin.

[0037] In this invention, the thickness of the conductive resin layer is not particularly limited and can be 3.0 μm or more, 5.0 μm or more, or 8.0 μm or more, and can be 100.0 μm or less, 80.0 μm or less, 60.0 μm or less, or 40.0 μm or less.

[0038] In this invention, the ratio of the conductive filler to the conductive resin constituting the conductive resin layer is not particularly limited, and can be 5.0% or more by mass, 10.0% or more by mass, or 15.0% or more by mass, and can be 40.0% or less by mass, 35.0% or less by mass, or 30.0% or less by mass.

[0039] The conductive resin layer of the present invention can contain any component. The resin may, for example, be insoluble in the battery electrolyte. The resin may, for example, contain at least one selected from the group consisting of olefin resins, urethane resins, polyamide resins, cellulose resins, polyether resins, acrylic resins, and polyester resins. The resin may, for example, contain at least one selected from the group consisting of polyethylene (PE), polypropylene (PP), polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), polyamide (PA), polyamide-imide (PAI), polyimide (PI), aromatic polyamide (aramid), liquid crystal polyester, polyacrylate, polymethyl methacrylate, polystyrene, AS resin, ABS resin, polyphenylene ether (PPE), silicone resin, and their modifiers. The modifier may, for example, be a maleic acid modifier. Through modification, for example, adhesion can be enhanced. The PE may, for example, contain linear low-density polyethylene (LLDPE), high-density polyethylene (HDPE), etc. For example, from the viewpoint of electrolyte resistance and moldability, LLDPE is suitable for resin materials.

[0040] In this invention, the conductive filler is not particularly limited and can be metal particles, carbon particles, etc. The conductive filler may include, for example, at least one selected from the group consisting of carbon black, spherical graphite, artificial graphite, vapor-grown carbon fiber (VGCF), carbon nanotubes (CNT), carbon nanofibers (CNF), carbon nanospheres (CNS), Ni particles, Sn particles, Cu particles, Ni-Sn alloy particles, Cu-Sn alloy particles, and Cu-Ni alloy particles. The carbon black may include, for example, at least one selected from the group consisting of acetylene black (AB), Ketjen black (registered trademark), furnace black, channel black, lamp black, and thermal black.

[0041] The shape of conductive fillers is not particularly limited; for example, they can be spherical, needle-shaped, or plate-shaped. The particle size D of the conductive filler... 50 There are no particular limitations; the particle size can be 1.0 μm or larger, 3.0 μm or larger, 5.0 μm or larger, or 7.0 μm or larger, and can be 15.0 μm or smaller, 10.0 μm or smaller, or 8.0 μm or smaller. Furthermore, in this invention, the particle size D... 50 The median particle size is the particle size at the 50% cumulative value of the particle size distribution of the volume reference obtained by laser diffraction and scattering.

[0042] <Aluminum vapor deposition film>

[0043] In this invention, the aluminum vapor-deposited film layer is contained within the electrode current collector. In this invention, the aluminum vapor-deposited film is a film formed by vapor-depositing aluminum onto the surface of a conductive resin layer.

[0044] The proportion of aluminum in the aluminum vapor-deposited film is not particularly limited; it can be 99.0% or more by mass, 99.3% or more by mass, or 99.5% or more by mass, and can be less than 100.0% by mass, less than 100.0% by mass, less than 99.9% by mass, or less than 99.8% by mass. The aluminum constituting the aluminum vapor-deposited film may contain impurities such as silicon, iron, copper, zinc, chromium, magnesium, calcium, and lead. In this invention, the content of each impurity can be determined by atomic absorption spectrometry (AAS) or inductively coupled plasma-atomic emission spectrometry (ICP-AES).

[0045] In this invention, the thickness of the aluminum vapor-deposited film is not particularly limited and can be 0.05 μm or more, 0.10 μm or more, 0.20 μm or more, or 0.30 μm or more, and can be 1.00 μm or less, 0.90 μm or less, 0.80 μm or less, or 0.60 μm or less. From a cost perspective, a thickness within the above range is preferred. Furthermore, in this invention, the thickness of the aluminum vapor-deposited film is a value measured by cross-sectional SEM observation.

[0046] In this invention, there is no particular limitation on the method for forming the aluminum vapor deposition film layer; it can be formed by vacuum vapor deposition, sputtering, CVD, etc.

[0047] <<Sodium Bipolar Electrode Laminate>>

[0048] The sodium bipolar electrode stack of the present invention includes the electrode current collector described in the present invention.

[0049] The sodium bipolar electrode laminate of the present invention can have a positive active material layer on one side and a negative active material layer on the other side of the electrode current collector described in the present invention. For example, when using an aluminum layer as the metal foil layer of the electrode current collector of the present invention, the negative active material layer can be on the metal foil layer side and the positive active material layer can be on the aluminum vapor-deposited film layer side, or the positive active material layer can be on the metal foil layer side and the negative active material layer can be on the aluminum vapor-deposited film layer side.

[0050] As the positive electrode active material layer and negative electrode active material layer in this invention, known positive electrode active material layers and negative electrode active material layers used in secondary batteries can be used.

[0051] The invention will be described in more detail with reference to the embodiments shown below, but the scope of the invention is not limited to these embodiments.

[0052] [Example]

[0053] <<Example 1>>

[0054] <Fabrication of Electrode Current Collectors>

[0055] (Preparation of conductive resin)

[0056] Carbon particles (D) 50 =7μm, artificial graphite) and linear low-density polyethylene (LLDPE) as resin were mixed and then melt-blended in a biaxial extrusion mixer at a mixing temperature of 200°C. At this time, the mixing ratio (mass ratio) was resin:carbon particles = 80:20. Thus, a conductive resin was produced.

[0057] (Layering of conductive resin and metal foil)

[0058] In an extrusion laminator, the resin composition is heated to 320°C to form a molten conductive resin. The molten resin is extruded from a T-die into a film, forming a conductive resin film. By passing this conductive resin film and a metal foil (Al foil, thickness: 35.0 μm) through the roller gap, an electrode current collector with a metal foil and a conductive resin layer as a conductive resin film is fabricated. At this time, the thickness of the conductive resin layer is 10.0 μm.

[0059] (Evaporation of aluminum vapor-deposited film)

[0060] An aluminum vapor deposition film was formed using a vacuum evaporation apparatus. The thickness of the aluminum vapor deposition film was determined by cross-sectional SEM observation, and the thickness was 0.10 μm. The aluminum content in the aluminum vapor deposition film was 99.0% by mass.

[0061] <Coating of the active material layer>

[0062] A negative electrode active material layer containing hard carbon as the negative electrode active material is coated on the side of the aluminum vapor-deposited film layer of the electrode current collector. Furthermore, a positive electrode active material layer containing a positive electrode active material for sodium batteries, comprising Ni, Fe, and Mn, is coated on the electrode terminals.

[0063] <Fabrication of Electrode Laminates>

[0064] An electrolyte was prepared containing 1.0 mol / L NaPF6 with a ethylene carbonate: methyl ethyl carbonate: dimethyl carbonate ratio of 3:3:4. Figure 1 As described, the electrode terminal 500 and the electrode current collector 100 are arranged such that the positive electrode active material layer 200 and the negative electrode active material layer 300 face each other. At this time, a diaphragm 400 is disposed around the portion of the electrode terminal 500 containing the positive electrode active material layer 200. The area around the electrode current collector 100 is sealed with a resin sealing member 600, and electrolyte is injected into the space containing the positive electrode active material layer 200 and the negative electrode active material layer 300. In this way, a single-layer electrode laminate is fabricated, simulating a bipolar electrode laminate where the electrolyte does not flow to the back of the electrode current collector. Here, Figure 1 (a) is a top view of the electrode stack of this embodiment. Figure 1 (b) is Figure 1 (a) shows a sectional view of line segment A, then Figure 1 (c) is Figure 1 (a) is a cross-sectional view of line segment B shown.

[0065] <<Examples 2-4>>

[0066] Examples 2 through 4 were carried out in the same manner as Example 1, except that the thicknesses of the metal foil layer, the conductive resin layer, and the aluminum vapor-deposited film layer were changed to those described in Table 1 below.

[0067] <<Comparative Example 1>>

[0068] Comparative Example 1 was performed in the same manner as Example 1, except that the thickness of the metal foil layer was changed to that described in Table 1 below and that it did not include the conductive resin layer and the aluminum vapor deposition layer.

[0069] <<Comparative Example 2>>

[0070] Comparative Example 2 was performed in the same manner as Example 1, except that the thicknesses of the metal foil layer and the aluminum vapor-deposited film layer were changed to those described in Table 1 below and the conductive resin layer was set as a carbon particle layer.

[0071] <<Evaluation>>

[0072] <Pinhole Test (Leakage Rate)>

[0073] The fabricated current collector foil was bent 180°, and then bent again at a right angle of 90°. After unbending the current collector foil, the presence of pinholes at the bend intersection was investigated. At the bend intersection of the current collector foil, approximately 15cm... 2 1.0 g of electrolyte was placed within a certain range, and it was observed for 10 minutes whether the electrolyte leaked under the current collector foil. The proportion of leaked electrolyte was used as the leakage rate for evaluation.

[0074] <Evaluation of Electrode Laminates (Initial Charge / Discharge Efficiency)>

[0075] For the first charge, a CCCV charge was performed at 0.05C to 4.2V. At this point, the charge was increased to the equivalent of 0.02C. Then, for the first discharge, a CC discharge was performed at 0.05C to 2.0V. The first charge / discharge efficiency (%) was calculated using the following formula: (First charge / discharge efficiency) = (First discharge capacity) / (First charge capacity) × 100

[0076] The implementation conditions and evaluation results of Examples 1 to 4 and Comparative Examples 1 and 2 are recorded in Table 1 below.

[0077] [Table 1]

[0078]

[0079] According to Examples 1-4 and Comparative Example 1, by including a conductive resin layer in the electrode current collector, the leakage rate was reduced. This confirmed that it is possible to suppress the formation of cracks and pinholes in the electrode current collector.

[0080] Furthermore, the initial charge-discharge efficiency of the electrode stack using the electrode current collector of Comparative Example 2 decreased, while the volume resistivity increased. This is believed to be because the surface of the conductive resin layer of the electrode current collector has a carbon particle layer.

[0081] Based on the above, it is confirmed that the electrode current collector with a conductive resin layer and an aluminum vapor-deposited film layer can be used as a sodium electrode current collector.

[0082] Symbol Explanation

[0083] 100 - Electrode current collector, 200 - Positive electrode active material layer, 300 - Negative electrode active material layer, 400 - Separator, 500 - Electrode terminal, 600 - Resin sealing component.

Claims

1. An electrode current collector, which is used in sodium batteries, characterized in that, It consists of a metal foil layer, a conductive resin layer, and an aluminum vapor-deposited film layer stacked in sequence.

2. The electrode current collector according to claim 1, characterized in that, The thickness of the aluminum vapor-deposited film layer is greater than 0.10 μm and less than 1.00 μm.

3. The electrode current collector according to claim 1, characterized in that, The conductive resin layer comprises resin and carbon particles dispersed in the resin.

4. The electrode current collector according to claim 1, characterized in that, The metal foil layer is an aluminum layer.

5. A sodium bipolar electrode laminate, characterized in that, The electrode current collector is provided with any one of claims 1 to 4.

Citation Information

Patent Citations

  • Sodium ion battery

    JP2010225525A

  • Electrode collector, bipolar battery, all-solid battery and method for manufacturing electrode collector

    JP2024088043A